2013
DOI: 10.5172/conu.2013.44.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on provider behaviors: A qualitative study of sexual and gender minorities regarding quality of care

Abstract: Lesbian, gay, bisexual, transgender, and queer (LGBTQ) identified patients report receiving substandard care from healthcare providers. They face the fear and disturbing reality of discrimination when accessing health care. Without culturally sensitive treatment, nursing and other health professions do not properly care for this population. Following the recent trend towards awareness and need for inclusion of LGBTQ populations in healthcare, this paper provides a summary of the current literature on the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(50 citation statements)
references
References 5 publications
3
47
0
Order By: Relevance
“…This finding suggests that communication barriers to sexual health services tied to anticipated heterosexist bias documented among older sexual minority patients 2191516171819 begins as early as 14 years of age. Importantly, we found that youth who reported that a provider had asked them questions about their sexual attractions or orientation reported higher levels of sexual health care communications and receiving HIV and STI preventive services, including HIV testing.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This finding suggests that communication barriers to sexual health services tied to anticipated heterosexist bias documented among older sexual minority patients 2191516171819 begins as early as 14 years of age. Importantly, we found that youth who reported that a provider had asked them questions about their sexual attractions or orientation reported higher levels of sexual health care communications and receiving HIV and STI preventive services, including HIV testing.…”
Section: Discussionmentioning
confidence: 88%
“…Barriers to receiving health care reported by older MSM include fear of sexual minority stigma or rejection by healthcare providers and failure of physicians to ask about sexual attractions 1516171819 . The few studies that have begun to address adolescent sexual health services among sexual minorities have not focused on AMSM exclusively, but rather, pooled lesbian, gay and bisexual adolescent and young adult populations.…”
Section: Introductionmentioning
confidence: 99%
“…Rounds et al examined behaviors of healthcare providers that improve or impede quality of care. [31] The participants were SGM patients who had seen a healthcare provider in the past year. Focus groups were conducted to discuss positive and negative interactions with healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…The study found the main barriers to care were a lack of provider knowledge and providers lack of inquiry about patient’s preferences for care. [31] Kitts surveyed physicians regarding LGBTQ adolescent health and found gaps in the practice, knowledge and attitudes of physicians. [26] Few physicians felt that they had the skills needed to address issues of sexual orientation.…”
Section: Discussionmentioning
confidence: 99%
“…For youth, the process of disclosing to healthcare providers can be as challenging as disclosing to friends and family (Law, Mathai, Veinot, Webster, & Mylopoulos, 2015). While multiple qualitative studies have examined experiences of disclosure for LGBTQ populations (Beehler, 2001; Hitchcock & Wilson; 1992; Law et al, 2015; Rounds, Burns, Mcgrath, & Walsh, 2013), few have focused specifically on the disclosure experiences of young adults.…”
Section: Healthcare and Patient Factors Influencing Disclosurementioning
confidence: 99%